ROSAGROSKRYNNIK, OR WORD PLAY POTENTIAL OF ABBRE¬VIATION (Proceedings of Southern Federal University. Philology, 2013)
Ilyasova S.V.Keywords: word play, word-formation, abbreviation, avalanche word- creation.The paper analyses methods of word play with abbreviations in the language of contemporary Russian mass media - word play decoding of abbreviations (diabbreviation), word-formation, based on abbreviation, creation of abbreviations of evaluative character. It presents such new abbreviation phenomena as avalanche word-creation, cliched graphoderivatives.